Otolith morphology of sprat (Sprattus sprattus) along the Swedish west coast - Saltalamacchia, Francesco (SLU/Dept. Of Aquatic Resources, 2018)
The population structure of sprat (Sprattus sprattus) in the Swedish Kattegat – Skagerrak has been at present not well investigated, and the boundaries between the management unit in this region and the larger stock occurring in the North Sea are also highly uncertain, posing issues to the successful management of the stock in this area.